2007
DOI: 10.1007/s10530-007-9123-z
|View full text |Cite
|
Sign up to set email alerts
|

Range expansion and population dynamics of co-occurring invasive herbivores

Abstract: Although a range of studies have suggested that competition plays a critical role in determining herbivore assemblages, there has been little work addressing the nature of interactions between competing invasive herbivores. We report the results of research on the hemlock woolly adelgid Adelges tsugae ('HWA') and elongate hemlock scale Fiorinia externa ('EHS'), invasive herbivores that both feed on eastern hemlock (Tsuga canadensis). HWA has been linked to hemlock mortality throughout the East Coast of the US;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…The experiment took place in Cadwell Forest (Petersham, Massachusetts, USA), a research forest managed by the University of Massachusetts. Although this location is south of the current northern range limit of both HWA and EHS (Preisser et al 2008), repeated surveys of the forest itself have found neither insect (J. Elkinton, unpublished data). Because HWA and EHS occur in forests to both the north and south of Cadwell Forest, we were given permission to carry out our experiment.…”
Section: Experimental Designmentioning
confidence: 95%
See 4 more Smart Citations
“…The experiment took place in Cadwell Forest (Petersham, Massachusetts, USA), a research forest managed by the University of Massachusetts. Although this location is south of the current northern range limit of both HWA and EHS (Preisser et al 2008), repeated surveys of the forest itself have found neither insect (J. Elkinton, unpublished data). Because HWA and EHS occur in forests to both the north and south of Cadwell Forest, we were given permission to carry out our experiment.…”
Section: Experimental Designmentioning
confidence: 95%
“…In light of research showing that landscape-level hemlock health has not declined as quickly as initially predicted (Preisser et al 2008), we hypothesized that for HWA-infested eastern hemlocks, the benefit of EHS co-infestation (reduced HWA density via exploitative competition) outweighs the resourcerelated costs of EHS presence. We predicted that plant growth should be highest in the control, but that plant growth in the HWA þ EHS treatment should be greater than in the HWA-only treatment but less than in the EHS-only treatment.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations